Analisis Komparasi Web Stack Berbasis Javascript pada Fase Konstruksi Aplikasi: MEAN, MERN dan MEVN - Koko Wahyu Prasetyo; Bima Reynaldi Sumitro (LPPM UBHINUS MALANG, 2025)
The construction phase of a web application development generally involves a number of personnel with specific perspectives and expertise, including: backend developers, frontend developers, and mobile developers. Based on these different perspectives, the combination of technology architecture and programming languages (stack) used will vary. Javascript is one type of programming language that is compatible with various platforms and can be used to harmonize the programming architecture of the three different perspectives. There are three types of JavaScript-based tech stacks that have a large user base: Angular-based MEAN, React-based MERN, and Vue-based MEVN. Based on this situation, it is necessary to empirically analyze tech stack comparisons in the context of web application development activities. The indicators used in this comparative study include: LOC (lines of code), execution performance, function structure analysis (call stack), and memory usage efficiency. The comparative results show that the MERN stack, which is based on React, has a more efficient LOC than the other two stacks. Though the difference is not very noticeable, MERN stack also displays the most efficient level of memory use. The comparative results also demonstrate that, in comparison to the other stacks, the MEVN tech stack has the most effective function call structure.